What Are the Rate and Risk Factors for Developing a Complication With the Pavlik Method for the Treatment of Hip Dysplasia?. Issue 10 (16th November 2021) - Masrouha, Karim; Gibon, Emmanuel; Roof, Mackenzie A.; Castañeda, Pablo
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The Pavlik method for the treatment of developmental dysplasia of the hip (DDH) has been proven successful for over 85 years. The high success rate and reproducibility have made it the mainstay of treatment. Methods: We performed a retrospective cohort study of patients with DDH treated with the Pavlik method between September 2016 and August 2018 with at least 24 months of follow up in a single academic center. We excluded patients with neuromuscular conditions, teratologic dislocations, and arthrogryposis. We identified and included a total of 307 patients in the analysis. There were 66 patients with dysplasia, 97 with instability, and 144 with a dislocation. Data collected included age at initiation of the Pavlik method, diagnosis (isolated dysplasia, subluxation, or dislocation), duration of treatment, follow up duration and any complication. At final follow up, anteroposterior radiographs of the pelvis were used to determine the Severin classification. Results: Major complications were proximal femoral growth disturbance (5.8%) and femoral nerve palsy (0.98%). Multivariate analysis showed that an initial diagnosis of a dislocated hip (odds ratio, 2.20; P <0.01), was significantly associated with developing a complication. At final follow up, we found Severin type I or II radiographic findings in 100% of patients with dysplasia, 95% of patients with instability and 54% of patients with dislocation ( P =0.001). Conclusions: Complications are not entirely uncommon when the Pavlik method is used for the treatment of DDH. The overall rate of major complications was 7%. The Pavlik method is safe, and independent risk factors for complications were being over 5 months of age and having a dislocated hip at initial presentation. Level of Evidence: Level IV—cohort study.